1983
DOI: 10.1524/ract.1983.33.23.145
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Astatine Chemistry: Formation of Complexes of Astatine

Abstract: Astatine-211At)ICoordination chemistry SummaiyThe natuie and ptopeities of inorganic "' At-species formed in aqueous solutions under alkaline, neutral, acidic and oxidative conditions are studied through extraction of At with a variety of organic solvents, followed by the determination of the cjuomatographic, re-extraction and interaction behaviour of the extracted activity. It is concluded from the R{ values (on SiO,) and the different affinities for a large amount of additives, that the extracted activity -f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Such a diatomic species is, however, unlikely to exist considering the range of astatine concentrations studied. 41 Furthermore, our investigations using quantum chemistry methods show that the expected standard potential of the At 2 /At -couple, about 0.18 V vs NHE, could not correspond to the measured redox potential, 0.36 ( 0.01 V. Hence, the exchange of two electrons rather shows the formation of At(I). Its presence as the cationic species At + will notably explain the ability of the species to react with halogen anions to form AtX m n-species.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Such a diatomic species is, however, unlikely to exist considering the range of astatine concentrations studied. 41 Furthermore, our investigations using quantum chemistry methods show that the expected standard potential of the At 2 /At -couple, about 0.18 V vs NHE, could not correspond to the measured redox potential, 0.36 ( 0.01 V. Hence, the exchange of two electrons rather shows the formation of At(I). Its presence as the cationic species At + will notably explain the ability of the species to react with halogen anions to form AtX m n-species.…”
Section: Discussionmentioning
confidence: 70%
“…The standard potential extrapolated at pH ) 0 is 0.74 ( 0.01 V. This value appears coherent with those published in the literature. 3,41 …”
Section: (A) Species I/species IImentioning
confidence: 99%
“…The chemical form of this species remains a subject of discussion [18]: whereas Visser et al described the extraction of astatine from nitric acid into DIPE by an interaction of the neutral complex AtO(NO 3 ) with the organic solvent [15], a similar extraction mechanism was proposed by Yordanov et al [12] by considering the extraction of the complex AtO 2 (NO 3 ) with astatine present at the oxidation state +V. In this study, considering the discrepancies reported in the literature, astatine is represented by the At(x) + species.…”
Section: General Considerations On Astatine Extractionmentioning
confidence: 99%
“…A simple kit for wet recovery of astatine-211 has been proposed [12]. The principle is to use the ability of astatine to be efficiently extracted in the organic solvents (dibutylether, carbon disulfide, benzene, methyl-isobutyl-ketone) from acid solutions (nitric acid, perchloric acid, acetic acid) [12][13][14][15]. The mechanisms of these solvent extractions and the chemical nature of astatine species involved in this process remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…These forms of astatine were determined at low concentration with chemistry techniques that can be used at a tracer level such as co-precipitation, liquid extraction, or electromigration experiments, with the knowledge of iodine chemistry as a guide. Most of the descriptions of the oxidation states presented below rely on works by Johnson et al, 19 Appelman, 20 Visser and Diemer, 21,22 and Dreyer et al [23][24][25] Also, more exhaustive information can be found in the DOESponsored Nuclear Science Series monogram by Ruth et al 26 At(-I). The (-I) oxidation state is probably the most clearly established form of astatine with a strong similarity with iodide.…”
Section: Inorganic Chemistry Of Astatinementioning
confidence: 99%